If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x = 12x + 18 Reorder the terms: 10x = 18 + 12x Solving 10x = 18 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 10x + -12x = 18 + 12x + -12x Combine like terms: 10x + -12x = -2x -2x = 18 + 12x + -12x Combine like terms: 12x + -12x = 0 -2x = 18 + 0 -2x = 18 Divide each side by '-2'. x = -9 Simplifying x = -9
| log(x-2)-log(2x-9)=0 | | 0.67x-12=18 | | 0/8x7 | | 12x+10=170 | | 3(-1/6)(-2/5)= | | 4+6=4+6 | | 11=-5+2x | | f(3a)=8x-6 | | 2a+b=5a+8b | | (-4)(-3)(-2)= | | 20/28=5/x | | 7n^3+49n=0 | | 3x+4=6x+8 | | 3(2+q)+15=q | | xsquared-5x=9 | | 1x+7y=36 | | f(x)=5x^5+x^4-27x^3-13x^2+134x+120 | | 3(-1/2)(-2/5 | | 0.2x+0.8= | | -4y=168 | | 0.5x+10=16 | | (x+7)+(3x-7)= | | 2/3•4 | | 25/135=x/27 | | 6y-=27-y | | v+16=2v | | 0.1d+0.3(d-7)=8.55 | | (4/7)x(4/8) | | 1/2x-13 | | -6-2(6n+4)= | | H=-3t^2+90t | | 6.4r-2.9r=r |